Altered White Matter Integrity in ADHD Revealed by Meta-analysis of Tract-based Spatial Statistics. Issue 9 (July 2023) - Cui, Jian; Wang, Zhonggang; Xu, Yinghong; Li, Ying; Yu, Hao; Ping, Liangliang; Jin, Shushu; Cheng, Yuqi; Xu, Xiufeng; Zhang, Yuebing; Zhou, Cong
Objective: We conducted an updated coordinate-based meta-analysis (CBMA) to determine the most prominent and robust white matter (WM) abnormalities in ADHD based on tract-based spatial statistics (TBSS) findings. Method: The seed-based d mapping (SDM) software was applied to compare regional fractional anisotropy (FA) alterations in ADHD. Subgroup meta-analyses in the pure ADHD without comorbidity subgroup, the children and adolescents subgroup, and the adults subgroup were also explored, respectively. Meta-regression analysis was subsequently used to examine potential correlations between demographics and FA changes. Results: Only one cluster in the splenium of corpus callosum (CC) exhibited age-related FA decrease in ADHD individuals in the pooled meta-analysis. The adults ADHD subgroup revealed two clusters with reduced FA lied in the splenium and body of CC. Conclusion: This updated CBMA confirmed the WM abnormalities in the splenium of CC in ADHD, and improved our understanding of the pathogenesis of this neurodevelopmental disorder.